The Essene Hypothesis: Insights from Religion 101 - Klawans, Jonathan (Dead Sea discoveries, 2016)
General insights from the discipline of religious studies may contribute to a better understanding of the Essene Hypothesis. In its “softer” form, the Essene hypothesis posits a sub-group relationship between the Qumran community and a larger Essene movement as described, above all, by Josephus. This effort to accommodate differences between accounts of the Essenes and the Scrolls can be better understood when contextualized in light of the so-called “insider/outsider” problem. Josephus’s use of the term “Essene” can be productively compared to generalized labels for groups of sub-groups, like “Quaker,” “Mormon,” “Hasidic” and “Gnostic”—terms used more often by outsiders, and frequently by writers of introductory religion textbooks. The Essene Hypothesis makes a greater deal of sense when seen in light of the ways generalized labels are used in a variety of descriptions of religious groups, both ancient and modern.